ANALISIS POTENSI BUMDES MELALUI PENGEMBANGAN BAMBU SEBAGAI OBJEK WISATA DI DESA SENDIR KECAMATAN LENTENG KABUPATEN SUMENEP - Kusuma, Nailah Aka; Malia, Evi (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2020)
The research is aims to make bamboo potential as a tourist attraction that supports government programs that will make Sumenep atourism city. Research method is descriptive qualitative method with data collection methods using interviews and field observation at Sendir vilage, Kecamatan Lenteng, Kabupaten Sumenep. Analysis of the data is using the miles and hubberman method. First with data reduction, data presentation and starting conclusions. The results of this research are Desa Sendir has the potential to be used as a tourist attraction with bamboo as a tourist attraction in terms of tourism potential sources. Facilities, and Ancillary . Desa Sendir must consider several inhibiting factors to find a solution so that the formation of a bamboo tourism village in Desa Sendir supported by all parties, tourism community and the government.